Closed‐leg standing long leg radiographs can be a useful tool to assess whether the joint line is parallel to the ground in restricted kinematic alignment total knee arthroplasty - Takashi Kobayashi; Kazumi Goto; Masayoshi Otsu; Kazuhiko Michishita (Journal of Experimental Orthopaedics, 2023)
Abstract Purpose Restricted kinematic alignment (rKA) is a modified technique of kinematic alignment (KA) total knee arthroplasty (TKA) for patients with an outlier or atypical knee anatomy, striving to preserve the native knee joint line parallel to the ground in a bipedal stance. This study aimed to evaluate the accuracy of rKA TKA with a computed tomography (CT)‐based patient‐specific instrument (PSI) to achieve the preoperative plan with the joint line parallel to the ground level. Methods Using a CT‐based PSI, 74 closed‐leg standing long‐leg radiographs were obtained before and after rKA TKA. The hip‐knee‐ankle angle (HKA), joint line orientation angle (JLOA), lateral distal femoral angle (LDFA), and medial proximal tibial angle (MPTA) were measured. Bone resection accuracy was evaluated by postoperative HKA deviations from the planned alignment and joint line by postoperative JLOA deviations from the ground level. Results The mean postoperative JLOA and HKA were 2.1° valgus (range, standard deviation: 6.0° valgus to 3.0° varus, 2.0) and 2.6° varus (3.5° valgus to 12.5° varus, 3.2), respectively. Postoperative JLOA and HKA were within ± 3° of the planned alignment for 69% and 86% of cases, respectively. Conclusions Despite a static verification, we clarified how the joint line after rKA TKA was reproduced in the closed‐leg long leg radiographs to mimic the limb position during gait. However, this imaging method is not well‐established, and lack of long‐term survivorship and the relationship between joint line inclination and clinical outcomes represented limitations of this study. Level of evidence Level IV.